Safety Inspections of Public Transport Modes in Accordance with Law No. 22 of 2009 Concerning Traffic and Road Transportation at the Service Unit of Type A Terminal in Bawen - Ayattullah Khumaini Abdul Rozak; Irfan Rizky Hutomo; Lailasari Ekaningsih; Ridho Sa’dillah Ahmad; Mohammad Tohari (Pusat Riset dan Inovasi Nasional, 2024)
Data collected from various sources indicates that traffic accidents remain a significant issue. The Indonesian National Police's Traffic Corps (Korlantas Polri) claims that the number of accidents across Indonesia has decreased over the past four years. This statement was made by AKBP Hendra Wahyudi, the Head of the Traffic Sub-Directorate, Ditgakkum. According to him, in 2019, the number of accidents reached 116,411 cases, which was higher than the 100,028 cases reported in 2020. In 2021, the number further decreased to 103,645 incidents, and by 2022, only 55,777 accidents had occurred.